Bituminous surface treatments - Castro, Jorge Arturo (2025)
Bituminous surface treatments (BST) built worldwide on a considerable percentage of total roads open to traffic year-round. Their low cost and possibility of execution using a wide range of local materials make these coatings very important, especially for light or medium traffic roads in rural areas. When construction done with appropriate equipment, result is first-quality pavement.